Deferoxamine enhances the migration of dental pulp cells via hypoxia-inducible factor 1α - Du, Rong (Am J Transl Res, 2021)
In previous studies, we found that deferoxamine (DFO) improved the migration of dental pulp cells (DPCs). The present study aimed to determine whether the effects of DFO on the migration of DPCs were regulated via hypoxia-inducible factor 1α (HIF-1α). Recombinant adenovirus vectors carrying short hairpin RNA (shRNA) targeting the human HIF-1α gene (pAd-GFP-shRNA-HIF-1α) and green fluorescent protein (GFP) were constructed. The expression of HIF-1α was inhibited by pAd-GFP-shRNA-HIF-1α at messenger RNA and protein levels. The secretion of stromal cell-derived factor 1α (SDF-1α) or vascular endothelial growth factor (VEGF) in DPCs treated with 10 μM DFO was higher than that in the control condition. The migration of DPCs was enhanced by 10 μM DFO. However, the effects of DFO on DPCs were partially reversed by silencing the HIF-1α gene in enzyme-linked immunosorbent assay or migration assay. Cumulatively, we conclude that DFO upregulated the secretion of SDF-1α or VEGF in DPCs and improved the migration of DPCs through HIF-1α.